Foreign banks and credit stability in Central and Eastern Europe. A panel data analysis - de Haas, Ralph; van Lelyveld, Iman (Journal of Banking & Finance, 2006)
We examine whether foreign and domestic banks in Central and Eastern Europe react differently to business cycles and banking crises. Our panel dataset comprises data of more than 250 banks for the period 1993–2000, with information on bank ownership and mode of entry. During crisis periods domestic banks contracted their credit base, whereas greenfield foreign banks did not. Also, home country conditions matter for foreign bank growth, as there is a significant negative relationship between home country economic growth and host country credit by greenfields. Finally, greenfield foreign banks’ credit growth is influenced by the health of the parent bank.